Pengaruh CAR, NPL, LDR Dan BOPO Terhadap Return on Aset (ROA) Pada Bank Umum BUMN Yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2019 - 2023 - Mubarokah, Mubarokah; Lusinto, Widodo Hari (Jurnal Bisnis dan Ekonomi, 2025)
This study aims to examine the effect of CAR, NPL, LDR and BOPO on the Return on Assets (ROA) of BUMN Banks listed on the Indonesia Stock Exchange. The population in this study were 4 BUMN Banks listed on the IDX. The type of data used in this study is secondary data obtained from the annual financial reports of BUMN Banks published on the Indonesia Stock Exchange for the period 2019-2023. The sampling technique in this study used purposive sampling, while the analysis method used was descriptive statistical analysis, in addition, the statistical analysis tool used for hypothesis testing was multiple linear regression.The classical assumption test showed that the normality test was normally distributed, the heteroscedasticity test did not show heteroscedasticity, the autocorrelation test did not show autocorrelation, and the multicollinearity test did not show multicollinearity. The results of the study using the F test showed that the model was suitable for use in the study, and hypothesis testing using the t test showed that the CAR variable had a significant positive effect on ROA, NPL had a significant negative effect on ROA, BOPO had a significant negative effect on ROA, and LDR had a positive and insignificant effect on ROA.